Sharia Bank’s Loyalty: Physical Evidence, Religiosity & Customer Intimacy Moderated by Brand Image and Switching Barriers - Ahmad Dzul Ilmi Syarifuddin; Abdul Hamid; Shakinah Shukri; Faqih Naufal (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study examines the impact of physical evidence, religion, and personal intimacy on customer loyalty at Bank Syariah Indonesia, while also assessing the moderating influence of brand image and switching barriers. The study employed a quantitative methodology to survey 230 clients. Data were gathered via a Likert-scale questionnaire and examined using SEM-PLS. The results demonstrated that brand image was the foremost determinant of customer loyalty, followed by physical proof and religiosity. Customer closeness did not exhibit a substantial direct impact on loyalty. Nonetheless, switching barriers, albeit not immediately impactful, acted as a moderator between physical evidence and consumer loyalty. The brand image substantially influences the relationship between religiosity and loyalty. This study contributes to the literature on sharia marketing by emphasizing the critical function of brand image in fostering customer loyalty and the significance of physical evidence in generating favorable customer experiences. The report offers strategic ideas for Sharia Bank management to elevate brand image, develop physical infrastructure, and incorporate Sharia principles into their services.